Does the student cost calculated by school reveal conditions of inequality or difference? - Ferraz, Jokasta Pires Vieira (Education Policy Analysis Archives, 2021)
The research problem that guides this study is: Does the cost-per-student, calculated individually for each school in the same municipal school system, reveal unequal or different financing conditions? In dialogue with other research, and specifically concepts of inequality and difference, this study was carried out with data from 185 municipal schools in the city of Curitiba for 2017 and 2016. The financial variables used in the research were: payroll for each school, resources for school meals, water bills, electricity and telephone, resources for school transport, values for each school by the Municipal Revolving Fund and by the Direct Money at School Program. The financial data were organized by school and a calculation was made by dividing the total cost of each by the number of students enrolled, which resulted in the cost per student-year of each school. The student cost was analyzed in conjunction with some context variables. The results are: average cost-student-year of R$ 8,145.20; the lowest student cost was R$ 4,556.06 and the highest was R$ 34,462.81.